(3eeGQSI GdSdWI GdJfajPjI ddGNJUGU GdJTQjYj aj GdfXGe GdOSJhQj GdchjJi (B: s (3OQGSI ebGQfI (B/ s - (3efjQI agO eOYK GdMGja GdfHgGf GdTeQis; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3jgJe Gdabg GdeYGUQ ddbGfhf GdOSJhQj HOQGSI eeGQSI GdSdWI aj GdTcd GdbGfhfj dgG aj GdOhdI, MjK Cfg dG jJUhQ eLJeY Ohf hLhO fXGe jfXe Ydi eNJda ChLg GdfTGW GdPj jeGQSg CaQGO gPG GdeLJeY, aGdSdWI HGYJHGQgG GdbhI GdeSjWQI Ydi GdeLJeY hfXGeg , hEP Cf XGgQI GdSdWI JhLO HGdJdGRe eY GdeLJeY, heY JbOe GdhYj GdSjGSj ddCaQGO jchf JfXje GdSdWI OGFekG aj EWGQ OSJhQj eGOj jcad Mbhbge hMQjGJge h jLYdge jQaVhf GdGSJHOGO h GdbeY, GdCeQ GdPj jZOh eYg GdMOjK Yf CfXeI SjGSjI JShO Gdjhe cGaI GdeLJeYGJ CeQkG dGRekG, hJCSjSkG Ydi Cf GdEWGQ GdOSJhQj GdPj JeGQS ajg GdSdWI COhGJgG jOhQ ehVhYg Mhd GdYdGbI Hjf GdSdWGJ hGdJj ef NdGdgG jecf JUfja GdCfXeI GdSjGSjI(B. (3hdCf GdSdWI gj MLQ GdRGhjI aj cd OhdI JJYOO aj ZGjGJgG hWQb eeGQSJgG eY JYOO GdCfXeI GdSjGSjI HJYOO Ohd GdYGde fLO GfgG JTJQc ajeG HjfgG HNUGFU YGeI, hGdJj jJjM OQGSJgG aj EWGQ hGMO GdJejjR Hjf GdCfXeI GdSjGSjI OSJhQjkG Ydi eYjGQ jLeY Hjf WQjbI JTcjd GdSdWI HGYJHGQgG GdLgGR GdSjGSj GdPj jYed OGNd GdfXGe hZGjGJ GdfXGe hCgOGag(B. (3hGYJeGOkG Ydi eG hUd Edjg GdJWhQ GdOSJhQj aj TCf GdJejjR Hjf GdCfXeI GdeYGUQI LGA GNJjGQ ehVhY HMKfG (B"(3eeGQSI GdSdWI GdJfajPjI ddGNJUGU GdJTQjYj aj GdfXGe GdchjJj(B" (3HZjI GdJYQa Ydi MbjbI GdhVY hGdJbjje GdOSJhQj dgPG GdfXGe(B. s
Contemporary jurisprudence of constitutional law is concerned with studying the exercise of power in its legal form in the state, as it cannot imagine a society without a system regulating the various aspects of the activity practiced by members of this society. And with the progress of the political awareness of individuals, the organization of power is always within a material constitutional framework that guarantees their rights and freedoms and makes them reject tyranny and oppression, which makes it necessary to talk about political systems that prevail today in all societies, and based on the fact that the constitutional framework in which power exercises its tools revolves around Its topic is about the relationship between the authorities through which political systems can be classified. And because power is the cornerstone of every state that has multiple objectives and ways of exercising it with the multiplicity of political systems in the multiplicity of countries of the world, we find that they share general characteristics, the study of which in one framework allows distinguishing between political systems constitutionally on a criterion that combines the method of forming power as the political organ that Works within the system and the aims and objectives of the system. And depending on what the constitutional development has reached regarding the distinction between contemporary regimes, the topic of our research was chosen, "The Executive Authority's Practice of Legislative Competence in the Kuwaiti System" in order to identify the reality of the situation and the constitutional evaluation of this system.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdYGe, (B2023s
. (3HHdjhLQGajG(B: (3UaMGJ (B489-510.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3eeGQSI GdSdWI GdJfajPjI ddGNJUGU GdJTQjYjs; (3Gdabg GdeYGUQ ddbGfhf GdOSJhQjs; (3XGgQI GdSdWIs; (3GdSdWg GdJfajPjg hGYOGO GdbhGfjf s; (3GdSdWg GdJfajPjg hGddhGFM GdJfajPjg s; (3abg GdbGfhf GdOSJhQi s; (3GdXQha GdGSJKfGFjg s; (3GdbGfhf GdchjJi s; (3GdQbGHg GdbVGFjgs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes